Development of professional expertise : toward measurement of expert performance and design of optimal learning environments - Ericsson, K. Anders (Cambridge University, 2013)
Professionals such as medical doctors, aeroplane pilots, lawyers, and technical specialists find that some of their peers have reached high levels of achievement that are difficult to measure objectively. In order to understand to what extent it is possible to learn from these expert performers for the purpose of helping others improve their performance, we first need to reproduce and measure this performance. This book is designed to provide the first comprehensive overview of research on the acquisition and training of professional performance as measured by objective methods rather than by subjective ratings by supervisors. In this collection of articles, the world's foremost experts discuss methods for assessing the experts' knowledge and review our knowledge on how we can measure professional performance and design training environments that permit beginning and experienced professionals to develop and maintain their high levels of performance, using examples from a wide range of professional domains